2023
DOI: 10.1002/aenm.202203509
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐Stage Sintered LLZO Scaffolds for Li‐Garnet Solid‐State Batteries

Abstract: While significant progress has been achieved in the field of Li‐garnet solid‐state batteries, their further development, is hindered by the formation of cavities at the Li7La3Zr2O12 (LLZO)/Li interface at practically relevant current densities and areal capacities exceeding 1 mA cm−2 and 1 mAh cm−2. As a result, the cells exhibit limited cycling stability due to the inhomogeneous distribution of the applied current density, and therefore, the formation of Li dendrites. Another aspect of high importance is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…These values align with those reported in existing literature, affirming consistency. 34 To explore the electrochemical behavior of self-standing porous LLZO membranes, symmetric Li/LLZO/Li cells were fabricated using the cold isostatic pressing of Li onto an LLZO membrane at ca. 71 MPa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values align with those reported in existing literature, affirming consistency. 34 To explore the electrochemical behavior of self-standing porous LLZO membranes, symmetric Li/LLZO/Li cells were fabricated using the cold isostatic pressing of Li onto an LLZO membrane at ca. 71 MPa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we have introduced a novel method for fabricating porous LLZO membranes known as intermediate-stage sintering. 34 This approach involves terminating the sintering process before full densification of the ceramics. A notable advantage of this process is the ability to achieve small pore sizes in LLZO ceramics without the need for pore formers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this regard, attempts have been made to fabricate thick (>10 μm) layers of porous solid electrolytes. [113,114] Bao et al successfully prepared a self-standing LLZTO ceramic skeleton with a thickness of 10−15 μm using a tape-casting method. [113] Further, Okur et al fabricated a porous LLZO scaffold with intermediate-stage sintering, without the use of any pore formers.…”
Section: Strategies To Minimize Anodic Stress Accumulation and Volume...mentioning
confidence: 99%
“…[113] Further, Okur et al fabricated a porous LLZO scaffold with intermediate-stage sintering, without the use of any pore formers. [114] Although these studies demonstrated that porous solid electrolytes can be produced, the porosity of the solid electrolyte would have to be much higher to fully utilize the benefits of 3D porous structures. Moreover, because solid electrolytes are theoretically not electron conductors, they should be coated with conductive agents to facilitate electrochemical reactions at the solid-electrolyte surface and reversibly store Li metal during charge and discharge.…”
Section: Strategies To Minimize Anodic Stress Accumulation and Volume...mentioning
confidence: 99%
“…Furthermore, before assembling the battery, a small amount of lithium metal must be vapor-deposited into the surface pores of the porous LLZO membrane to enhance the contact between the porous LLZO and the lithium anode. [28][29][30] The treatment process mentioned exhibits a high level of complexity, thereby hindering the advancement of porous LLZO-based SSLMBs.…”
Section: Introductionmentioning
confidence: 99%